Kriminalisasi Delik Perzinahan Dalam Undang-Undang Nomor 1 Tahun 2023 tentang Kitab Undang-Undang Hukum Pidana - Lade Sirjon; La Ode Awal Sakti (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2023)
The background of this study is the renewal of national criminal law with the enactment of Law Number 1 of 2023 concerning the Criminal Code. Referring to the Aquo Law, there are several criminalizations of an act, including related to adultery offenses. Thus, it is necessary to analyze the criminalization of adultery offenses based on Law Number 1 of 2023 concerning the Criminal Code. This study aims to explain the policy formulation of the criminalization of adultery offenses based on Law Number 1 of 2023 concerning the Criminal Code. This study employs a descriptive-normative research method. The results of the study show that the criminalization of adultery offenses in the Criminal Code has several expansions compared to the old Criminal Code. The expansion of the adultery offenses includes the meaning of adultery, cohabitation, and incest. The basic reason for this criminalization is that the renewal of law (Criminal Code) must be oriented towards the basic ideas of the Five Principles (Pancasila), which contain the values/ideas of divinity (religious morals), humanity, nationality, democracy, and social justice. In addition, the renewal of criminal law should also be carried out by exploring and studying unwritten sources of law and values that live in society, including religious law and customary law.